KEPASTIAN HUKUM TERHADAP HAK KEKAYAAN INTELEKTUAL YOUTUBER DALAM TRANSAKSI PEMBIAYAAN BANK MENGGUNAKAN KONTEN YOUTUBE - Sabijanto, Virly Vidiasti (LITIGASI, 2024)
This article examines the role of YouTube Content as an intellectual property asset (IP) in copyright transactions in banking financing, where the content is used as collateral. The main focus is on how copyrighted content, such as that found on YouTube, can enhance value and provide legal certainty on the assets in financing. Using normative juridical analysis and qualitative analysis methods, this research discusses regulations, expert views, and legal aspects related to Intellectual Property Rights (IPRs), with a specific focus on YouTube content. The research findings indicate that YouTube content has great potential as collateral in financing but is hindered by legal challenges such as determining the value of IPRs, copyright protection, and changing market dynamics. Government Regulation Number 24 of 2022 supports the creative economy through an IPR-based financing scheme, requiring legal awareness and collaboration among all stakeholders. The conclusion emphasizes the importance of proactive action by banks to protect copyrights when using YouTube content as collateral, as well as the importance of legal certainty to support creative economic actors. The implementation of these regulations is considered strategic to support the growth of the creative economy, with the protection and utilization of IPRs as key assets. Keywords:      Intellectual Property Rights, Bank Financing Transactions, YouTube Content as Collateral, Creative Economy Actors, Legal Certainty.